The influence of audio-visual media in the kangg's escape athletic learning program on PE learning motivation - Hadi Putra, Cahya; Ramadhana Sonjaya, Azhar; Arifin, Zaenal; Kurnawati, Ani (Mamaos:Journal Physical Education, Sport and Art, 2025)
This study reveals the positive impact of using audiovisual media in teaching Kang's Escape athletics to fourth-grade students at SDN 2 Suka Mukti. The main findings indicate a significant influence of audiovisual media on students' learning motivation, evidenced by a strong significance value (p < 0.05). This suggests that the use of videos, animations, or multimedia presentations in athletics learning can stimulate students' interest and enthusiasm, thus encouraging them to learn more actively and enthusiastically. The results of this study are in line with the importance of the role of learning media in creating effective and efficient teaching and learning processes. Audiovisual media, with its ability to present information in an interesting and interactive format, has proven to be able to overcome students' passive behavior and encourage active participation in learning. The use of this media is also in line with the differentiated learning approach that recognizes the diversity of students' needs and abilities, providing opportunities for each student to reach their maximum potential. Overall, this study confirms that the integration of audiovisual media in learning, especially in the context of Kang's Escape athletics, has a significant positive impact on students' learning motivation. These findings provide empirical support for educators to make better use of the potential of audiovisual media in creating a more conducive learning environment and motivating students to learn more diligently.